Mentalizing, Attachment, and Epistemic Trust in Group Therapy. Issue 2 (3rd April 2017) - Fonagy, Peter; Campbell, Chloe; Bateman, Anthony
ABSTRACT: This article sets out the relevance of recent theoretical developments in the areas of mentalizing, attachment and epistemic trust in relation to group therapy. It begins with an account of the role of mentalizing in the attachment context in the development of epistemic trust—defined as trust in the authenticity and personal relevance of interpersonally transmitted knowledge about how the social environment works. It then explains the particular way in which this emphasis on social communication is pertinent to group therapy and its function as a training ground for mentalizing and the initial experimentation with the opening of epistemic trust in a social context. The article finishes with an account of how mentalization-based group work is undertaken.